Scottish school spending, teachers and pupil numbers - Luke Sibieta; Darcey Snape (Institute for Fiscal Studies (IFS), 2025)
At just under 8 billion, spending on schools and childcare is the second-largest area of public service spending in Scotland, behind spending on health. While councils rather than the Scottish Government itself determine how much to spend on schools, they do so in the context of a funding and policy environment shaped by the Scottish Budget. With this context in mind, this chapter starts in Section 4.1 by describing trends in spending and spending per pupil, including comparisons with England. It then details trends in teacher and pupil numbers in Section 4.2. Section 4.3 describes the overall challenges and trade-offs facing policymakers in Scotland over the next few years, including for this and future Budget cycles. Section 4.4 provides a brief conclusion.
Keywords: 330; Education and skills; Government finances and spending; Devolved government finances; Education; Government spending; Local government finance; Scotland; Public finance